MOF-based ionic sieve interphase for regulated Zn2+ flux toward dendrite-free aqueous zinc-ion batteries. Issue 8 (2nd February 2022) - Wang, Yu; Liu, Yani; Wang, Haoqiang; Dou, Shuming; Gan, Wei; Ci, Lijie; Huang, Yan; Yuan, Qunhui
Abstract : A rationally designed multifunctional Zn3 (BTC)2 coating layer for Zn anodes to achieve dendrite-free aqueous ZIBs with high capacity and long lifespan. Abstract : Targeted at mitigating the inevitable dendrite growth and side reactions in zinc-ion batteries (ZIB), herein, a multifunctional protective strategy of Zn anode coating using zinc benzene tricarboxylate (Zn–BTC) is proposed in the Zn symmetric cell and MnO2 //Zn full cell. The rationally selected pores of Zn–BTC served as ionic sieves, accelerating the transport of Zn 2+ while blocking the entrance of the electrolyte anions. The structural grids of Zn–BTC hindered the two-dimensional diffusion of Zn 2+ and regulated the electric field at the anode, resulting in a uniform flux of Zn 2+ and subsequently stable stripping/plating. The Zn–BTC layer also worked as an artificial solid/electrolyte interphase film, expelled the solvated water molecules and restricted the side reactions. As a result, ultra-long cycling stability was achieved, with a superior lifespan of 800 h in the Zn symmetric cell and outstanding capacity retention of 81.1% after 1000 cycles in the MnO2 //Zn battery at a high current density of 2 A g −1 .